(untitled) (Journal of Kidney Cancer, 2025)
We report a case of a pathogenic variant c.463+4C>G in the von Hippel-Lindau (VHL) gene identified in a patient presenting with bilateral adrenal tumors, including a histologically confirmed pheochromocytoma with no significant family history of VHL-associated tumors. This same variant was first reported as having pathogenic significance in an unrelated proband with a hemangioblastoma and a family history of pheochromocytoma. In our patient, next-generation sequencing and subsequent RNA (ribonucleic acid) analysis confirmed this mutation to be a pathogenic (class 4) variant in intron 2. The lack of family history of VHL-associated tumors correlated with the proband further suggests that this mutation may have reduced penetrance. This case confirms the pathogenicity of the same previously described variant in the VHL gene and underscores the utility of genetic testing in patients with atypical presentations of adrenal tumors, even in the absence of a relevant family history.